161 DOES 2 DAYS OF BED REST CAUSE METABOLIC DETERIORATION?. (1st January 2005) - de Serna, Gonzalez D.; Schneider, S.; Burge, M.; Hall-Brabec, J.; Marriott, D.; Schade, D. S.
Abstract : Purpose: Hospital admission for illness is associated with metabolic deterioration for many patients with diabetes. Traditionally, this deterioration has been attributed to the illness-induced elevation of stress hormones. We examined the possibility that the inactivity associated with the bed rest per se also contributes to the metabolic deterioration. Our study examined whether 2 days of bed rest would result in an increase in insulin resistance in both normal and diabetic individuals as measured by the HOMA-IR index. Methods: We conducted a randomized, crossover study in 5 individuals with type 2 diabetes and 6 control individuals. Each subject completed 2 inpatient hospital admissions, one involving complete bed rest for 48 hours and one involving normal activity. The admissions differed only by the amount of activity allowed. During all admissions, subjects received three standard meals. Fasting laboratory tests, including glucose, insulin, C-peptide, and lipids, were performed each study day. (Table ) Results: The HOMA-IR (glucose × insulin / 22.5), which is an established measure of insulin resistance, increased significantly in both the normal and the diabetic volunteers. Conclusions: This study demonstrates that two days of bed rest alters metabolic control in both normal volunteers and patients with type 2 diabetes. Therefore, deterioration of metabolic control in patients with diabetes during the first 2 days of hospitalization is caused by both the bed rest and the stress of the illness.